The concept of the state in international relations : philosophy, sovereignty, cosmopolitanism - Schuett, Robert; Stirk, Peter M. R., 1954- (Edinburgh : Edinburgh University Press, 2015)
A critical reassessment of the concepts of the state and sovereignty in international relations theory. The concept of the state plays a central role in international relations, particularly in realist and neo-realist approaches. Yet, the meaning of the state is persistently taken to be self-evident by both advocates of the sovereign state and its critics. This volume counters this trend. It systematically considers the nature of the state, the concept of sovereignty and the challenges globalisation and cosmopolitanism. Featuring contributions from some of the most reputed theorists of the state, the essays in this collection give you a coherent and, at the same time, distinctively pluralist set of original reflections on the role and nature of the state.
Introduction: The concept of the State in international relations / Peter M.R. Stirk -- 1. International law and statehood: a performative view / Janis Grzybowski and Martti Koskenniemi -- 2. The State as a universe of discourse / Peter J. Steinberger -- 3. Sovereignty and the personality of the State / Jens Bartelson -- 4. The State as urban myth: governance without government in the global South / Oliver Jütersonke and Moncef Kartas -- 5. Decolonising sovereignty: globalisation and the return of hyper-sovereignty / John M. Hobson -- 6. The concept of the State as a community of liability / Peter M.R. Stirk -- 7. From global governance to global stateness / William E. Scheuerman -- 8. Open societies, cosmopolitanism and the Kelsenian State as a safeguard against nationalism / Robert Schuett.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: State, The; International relations; Sovereignty; État.; Relations internationales; Souveraineté.; international relations; sovereignty; PHILOSOPHY -- Political; International relations; Sovereignty; State, The; Staat; Souveränität; Internationale Politik; Politische Philosophie; Staat; Außenpolitik; Weltpolitik; Internationales politisches System; Internationale Politik; Souveränität.; Philosophie; Suveränitet.; Staten; Internationella relationer